FRI0584 Inter-Observer Agreement in the Quantitative Assessment of the Nailfold Capillaroscopic Findings in Systemic Sclerosis. (9th June 2015) - Di Donato, E.; De Angelis, R.; Salaffi, F.; Grassi, W.
Abstract : Background: Nailfold videocapillaroscopy (NVC) is a widely accepted technique used to assess microcirculation in patients with systemic sclerosis (SSc). However, very few studies have been focused in determining the variability of two different observers for the recognizing and scoring of the capillaroscopic findings by quantitative methods, as most of the authors has been working on qualitative and semi-quantitative evaluation. Objectives: To investigate the inter-observer agreement in the quantitative assessment of the most relevant capillaroscopic abnormalities in patients with SSc. Methods: Ten patients with diagnosis of SSc, according to the American College of Rheumatology criteria, were included in the study. All NVC examinations were performed blindly by two investigators with different experience in the field of NVC, at the second, third, fourth and fifth finger of both hands. Four consecutive images (one linear millimeter for each one) for all fingers were collected and stored, and the most visible was chosen. This image was examined to quantitatively assess the capillaroscopic parameters (number of dilated capillaries, total number of capillaries, number of microhaemorrhages, number of angiogenetic loops, and width of more dilated loop). The statistical analysis was made with MedCalc® version 12.4 (MedCalc software, Mariakerke, Belgium) for Widows XP. The inter-observer agreement was evaluated by weighted k (kw) for ordinal data (number of dilated capillaries, microhaemorrhages, and angiogenetic loops) and ICC-intraclass coefficient correlation (ICC) for quantitative data (number of loops and total width). Results: A total of 84 consecutive images were evaluated. The overall number of the tracked and examined capillaries was 470. The kw values (95% CI) and the ICC (95% CI) for quantitative data were as follows: number of dilated capillaries 0.909 (0.829- 0.938); number of micro-haemorrhages 0.885 (0.715-0.991); number of angiogenetic loops 0.943 (0.912-0.967), number of total loops 0.992 (0.993-0.998); width of more dilated loop 0.991 (0.975-0.993). Good to excellent inter-observer agreement was present for all parameters. The recognition of the number of micro-haemorrhages was the parameter with a relatively lower degree of concordance. Conclusions: Our data indicate a very good inter-observer agreement in the quantitative assessment of morphologic abnormalities by NVC in patients with SSc. This result demonstrate a high reproducibility of the capillaroscopy technique, which may be utilised in longitudinal studies to assess and quantify the microvascular damage, especially prior and after treatment with vasoactive drugs. References: Gutierrez M, Bertolazzi C, Tardella M, Becciolini A, DI Carlo M, Dottori M, Grassi W, De Angelis R. Interreader reliability in assessment of nailfold capillary abnormalities by beginners: pilot study of an intensive videocapillaroscopy training program. J Rheumatol. 2012 Jun;39(6):1248-55. Disclosure of Interest: None declared